(untitled) (Research, Society and Development, 2020)
The aim of this study was to evaluate the effect of sanitization on minimally processed cabbage (Brassica oleracea L.). This is a quantitative, descriptive and laboratorial study where the samples were submitted to three different processes: washing only in running water; washing in running water followed by the use of sodium hypochlorite-based sanitizer and, finally, washing in running water followed by sanitization using chlorinated compounds based on sodium dichloroisocyanurate. Subsequently, microbiological analyses of total coliforms Escherichia coli and Salmonella ssp. were performed. The results showed that the sodium hypochlorite-based solution did not present a reduction in microbial population, while those based on sodium dichloroisocyanurate allowed the reduction to safe levels for human consumption. A greater control in sodium hypochlorite-based products is suggested, since possibly this result was due to the low concentration of free active chlorine.